(untitled) (Al-Qamar, 2020)
The Christians started study of Islam at the time of revelation on prophet Muhammad (SAW). In the beginning some of their religious persons like Waraqah bin Nofil and Najashi confirmed that Muhammad (SAW) is the Prophet of God and the Holy Quran is a revealed book. But when Islam entered in Christians occupied areas (Syria, Egypt, Spain etc) and these areas went under the control of Muslims and the people of these areas started accepting Islam, the Christians started opposing Islam not only with weapons but also with pen. These opposing attitudes were on peak during the Crusade period and that attitudes are still alive in different forms. In this article, we discussed and analyzed the different periods of Christians’ study of Islam in historical perspective and tried to highlight the essence of their so called research and its methodology and concluded that their study is based on enmity and prejudice and not on facts and figures.